The The Influence of Investment Knowledge, Sharia Financial Literacy, and Siri' on Investment Interest in the Sharia Capital Market Coastal Communities in Palopo City: A Study on Coastal Communities in Palopo City - Dhea Resky Ananda; Jumawan Jasman; Sofyan Syamsuddin; Samsinar Samsinar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
The development of technology and the Islamic capital market in Indonesia shows great potential in driving economic growth based on Islamic principles. However, community participation, especially in coastal areas such as the city of Palopo, remains relatively low despite the development of regulations and instruments in the sharia capital market. Purpose: This study aims to analyze the influence of investment knowledge, sharia financial literacy, and Siri’ on investment interest in the sharia capital market, methodology: using a quantitative method. The research population includes the coastal community of Palopo City who have the potential to participate in sharia-based investment activities, using a non-probability sampling technique with a purposive sampling approach, while respondent selection was conducted thru incidental (accidental) sampling, resulting in 163 respondents. Data analysis was conducted using SmartPLS based on structural equation modeling (SEM) with a Partial Least Square (PLS) approach. Results: the research results show that investment knowledge is not urgent in influencing investment interest in the sharia capital market. On the contrary, sharia financial literacy and the value of Siri' are very urgent in influencing investment interest in the sharia capital market. Findings: sharia financial literacy and the cultural value of Siri’ become important factors that drive the community's interest in investing in the sharia capital market, whereas investment knowledge alone is not sufficient to increase investment interest. Novelty: this research integrates economic, religious, and local wisdom factors by incorporating the cultural value of Siri’ as a variable that influences investment interest in the sharia capital market. Originality: this research provides a new perspective in the study of sharia investment by examining the influence of the local Siri’ cultural values on investment interest in coastal communities. Conclusion: the investment interest of coastal communities in the sharia capital market is more influenced by sharia financial literacy and the value of Siri’ than by investment knowledge alone. Type of paper: Empirical research.